Evaluation of grout materials for CFRP ground anchors with strap ends. (1st August 2017) - Fan, Haifeng; Vassilopoulos, Anastasios P.; Keller, Thomas
Highlights: Complete stress-strain response of cement- and resin-based grouts. Experimental methods to obtain strain-softening response of grouts. Validation of applicability of concrete models to grouts. FE analyses of pull-out experiments on CFRP strap-end anchor heads. Influence of grout strain-softening behavior on pull-out response of anchors. Abstract: An evaluation of cement- and resin-based grout materials for applications in carbon fiber-reinforced polymer (CFRP) ground anchor heads composed of high-strength grout and a CFRP strap was conducted. Uniaxial compression experiments were performed on cylinder specimens. Appropriate loading-control methods and boundary conditions were determined in order to obtain the softening branch of the compressive stress vs strain curves. The concrete compression model developed by Sargin was successfully applied to also describe the compressive grout behaviors. The results of finite element analyses of the CFRP ground anchor head and implemented grout model compared well with experimental results. A parametric study based on different grout softening behaviors showed that only limited stress redistribution occurred after crack initiation.